2022
DOI: 10.3390/horticulturae8121138
|View full text |Cite
|
Sign up to set email alerts
|

Plant Performance and Soil Microbial Responses to Irrigation Management: A Novel Study in a Calafate Orchard

Abstract: Calafate fruits have a high content of phenolic compounds and an antioxidant activity up to four times higher than that of blueberries. The establishment of a calafate orchard and irrigation responses on fruit and soil characteristics have been scarcely studied. Therefore, the objective of this study was to evaluate the effect of water replenishment rate: 0%, 50%, 100% and 150% of reference evapotranspiration (ET0), on soil microbiological activity, plant physiological response, fruit yield and chemical compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…This study signifies a notable progression in the assessment of planting density in calafate orchards, as it illustrates the role of planting density in enhancing soil microbial and enzymatic activity, thereby influencing the antioxidant activity of calafate fruit (Betancur et al, 2022;. Nevertheless, due to their moderate interrelationships, a comprehensive analysis of these factors is warranted.…”
Section: Physicochemical Fruit Responsementioning
confidence: 75%
See 3 more Smart Citations
“…This study signifies a notable progression in the assessment of planting density in calafate orchards, as it illustrates the role of planting density in enhancing soil microbial and enzymatic activity, thereby influencing the antioxidant activity of calafate fruit (Betancur et al, 2022;. Nevertheless, due to their moderate interrelationships, a comprehensive analysis of these factors is warranted.…”
Section: Physicochemical Fruit Responsementioning
confidence: 75%
“…The lack of dehydrogenase response could also be explained by the high OM content in the soil at the beginning of the study. Although there was a higher OM content in HD, previous studies in the same area indicated that OM levels higher than 9% reached a threshold where there was no change in the activity of this enzyme (Betancur et al, 2022;. However, it is important to note that the response of these enzymes is more pronounced with fertilization treatments in soils with low fertility because it promotes the formation of organo enzyme complexes that improve their stability (Nannipieri et al, 2012).…”
Section: Chemical and Microbiological Soil Responsesmentioning
confidence: 86%
See 2 more Smart Citations
“…Data were expressed as mg 100 g −1 FW [36], a compound found in greater proportion in blueberry [31]. The DPPH antioxidant capacity was performed as described by Betancur et al [37], the extract was diluted, and the DPPH solution was incorporated and kept in the dark for 1 h at room temperature. The readings in the spectrophotometer were determined at 515 nm, and the standard curve used was 0.0008× + 0.0272 and R 2 = 0.99.…”
Section: Yield and Physical-chemical Parameters Of Fruitmentioning
confidence: 99%